2007
DOI: 10.1007/bf02685917
|View full text |Cite
|
Sign up to set email alerts
|

Decreased thiamine and magnesium levels in the potentiation of the neurotoxicity of lead in occupational lead exposure

Abstract: The relationship between blood lead (Pb) and serum levels of calcium and of neural nutrients such as thiamine and magnesium (Mg) has been determined in a Nigerian population that is occupationally exposed to Pb. Forty-seven male Pb workers were recruited as test subjects and 25 males unexposed to Pb served as controls. The test subjects were classified into three groups, based on severity of exposure to Pb. Blood lead (BPb) and the serum levels of Mg, thiamine, and calcium were determined in both test subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Several works has described calcium intake as protective factor that reduces blood lead levels in children (Lacasaña et al, ; Mahaffey et al, ) and decreases fetal lead accumulation (Han et al, ).In contrast to these studies, a population analysis among American women in reproductive age did not find calcium intake as predictor of blood lead levels, although it was found associated with thiamine intake, which in our study was marginally and inversely associated with blood lead levels in the upper quartile (Lee et al, ). This association with thiamine intake has been also reported in male workers occupationally exposed to lead (Iro et al, ), and decreased serum level of this vitamin has been associated with neurotoxicity by lead (Anetor et al, ). Although evaluation of the relationship between vitamin B12 dietary intake and blood lead levels has been scarcely studied or reported, a negative correlation between vitamin B12 and lead levels was described in amniotic fluid (Dawson et al, ).…”
Section: Discussionsupporting
confidence: 57%
“…Several works has described calcium intake as protective factor that reduces blood lead levels in children (Lacasaña et al, ; Mahaffey et al, ) and decreases fetal lead accumulation (Han et al, ).In contrast to these studies, a population analysis among American women in reproductive age did not find calcium intake as predictor of blood lead levels, although it was found associated with thiamine intake, which in our study was marginally and inversely associated with blood lead levels in the upper quartile (Lee et al, ). This association with thiamine intake has been also reported in male workers occupationally exposed to lead (Iro et al, ), and decreased serum level of this vitamin has been associated with neurotoxicity by lead (Anetor et al, ). Although evaluation of the relationship between vitamin B12 dietary intake and blood lead levels has been scarcely studied or reported, a negative correlation between vitamin B12 and lead levels was described in amniotic fluid (Dawson et al, ).…”
Section: Discussionsupporting
confidence: 57%
“…The abovementioned mechanisms explain increased calcium level reported in erythrocytes of workers chronically exposed to lead [ 16 ] and in human erythrocytes exposed to lead in vitro [ 17 ]. In accordance, a negative correlation ( R = −0.41, p < 0.01) between blood lead level and plasma calcium level was shown in workers chronically exposed to lead [ 20 ]. This observation may be also due to the inhibitory effect of lead on 1 α -hydroxylase in renal tubules.…”
Section: Discussionmentioning
confidence: 59%
“…Ten studies reported serum calcium levels, seven of them observed significantly lower calcium levels among Pb exposed group as against the control group 3 , 4 , 6 – 9 , 13 , 14 , 28 , 29 . The Pb exposed group exhibited − 0.72 mg/dl (95% CI − 0.36 to − 1.07, I 2 = 95.12%) lower calcium as compared to the comparative group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All recorded data were confirmed for consistency before executing further analysis. In situations where the outcome parameters were reported in unconventional/non-standard units, standard conversion factors were used for converting them to standard units 3 , 6 . The calcium, lead, vitamin D and parathyroid levels were converted to the SI units, i.e.…”
Section: Methodsmentioning
confidence: 99%